2021
DOI: 10.1098/rspb.2021.1632
|View full text |Cite
|
Sign up to set email alerts
|

When fossil clades ‘compete’: local dominance, global diversification dynamics and causation

Abstract: Examining the supposition that local-scale competition drives macroevolutionary patterns has become a familiar goal in fossil biodiversity studies. However, it is an elusive goal, hampered by inadequate confirmation of ecological equivalence and interactive processes between clades, patchy sampling, few comparative analyses of local species assemblages over long geological intervals, and a dearth of appropriate statistical tools. We address these concerns by reevaluating one of the classic examples of clade di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…This is in contrast to other empirical studies based on different taxa, which suggest that larva dispersal modes or geographic range sizes associated with them directly influence diversification rates ( 46 ). Rather, it could be “external” factors, such as the macroevolutionary influence from a competing clade, the cyclostomes, which drove their diversification ( 13 ), as suggested by a character-independent model of speciation and extinction ( Table 1 ). Alternatively, an unmeasured trait that is associated with brooding/nonfeeding larvae could be responsible for differential rates of diversification in cheilostomes (table S7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to other empirical studies based on different taxa, which suggest that larva dispersal modes or geographic range sizes associated with them directly influence diversification rates ( 46 ). Rather, it could be “external” factors, such as the macroevolutionary influence from a competing clade, the cyclostomes, which drove their diversification ( 13 ), as suggested by a character-independent model of speciation and extinction ( Table 1 ). Alternatively, an unmeasured trait that is associated with brooding/nonfeeding larvae could be responsible for differential rates of diversification in cheilostomes (table S7).…”
Section: Discussionmentioning
confidence: 99%
“…They represent c. 80% of the phylum’s living species diversity ( 12 ). Likewise, there are c. 7900 described fossil cheilostome species documented in a recent data compilation, where this number is a considerable underestimate of true fossil richness based on models that account for incomplete sampling in the fossil record ( 13 ). Their benthic, largely sessile and encrusting life habit allows us to investigate spatial competition frozen in geological time ( 14 ), and their modular and polymorphic nature permits the estimation of key biological parameters, including fitness components ( 15 ) beyond ecological time scales.…”
Section: Introductionmentioning
confidence: 99%
“…While the portion of TMO data that is derived from the taxonomic literature may be less plagued by taxonomic misidentifications, the same cannot be easily argued for faunal lists or ecological surveys, much of which DB data is based on. However, in our experience, broad inferences based on synoptic, large-scaled databases tend to change significantly with different models, more so than data updates ( Sepkoski, 1993 ; Liow, Reitan & Harnik, 2015 ; Lidgard et al, 2021 ).…”
Section: Discussionmentioning
confidence: 84%
“…Many species await description; Gordon et al (2019) suggest that there are over 6,400 known cheilostome species without commenting on nomenclatural status, suggesting that there are up to 600 known species that need naming. Yet, a recent study, based on bryozoans, comparing datasets with taxonomic synonyms and without, found that synonymization does not contribute to qualitative changes in broad scale inferences ( Lidgard et al, 2021 ). Our machine-classifier is currently unable to extract location information for 21% of the species that were detected in our corpus of published works ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The import of interspecific competition in both evolution and ecology has long been recognized [1,2], but the capacity for biotic interactions at the organism and population level to impact directly upon species richness remains an open question [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%